Pengaruh Konsentrasi Pelarut Asam (HNO3 dan CH3COOH) dan Temperatur Terhadap Persen Recovery Nikel Dari Hasil Leaching Bijih Laterit Morowali - Alexander Malau; Nurul Halizah; Gogo Pasaribu; Hendi Lilih Wijayanto; Ardiansah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
One of the largest nickel producing areas in the world is Morowali, Indonesia. Stainless nickel is the raw material for battery cathodes and is also used as its precursor. In this study, Morowali laterite ore was extracted through a process known as solid-liquid extraction (leaching). Nitric acid and acetic acid solvents were used for the leaching process. The purpose of this research was to determine the effect of concentration and temperature of leaching acid solution on the percent recovery of nickel produced. Leaching was carried out with variations in concentration and temperature. In this study, the method used was acid leaching at atmospheric pressure (APAL). The results of this study indicate that increasing acid concentration and leaching temperature increases the percent recovery of nickel obtained. The best concentration and temperature from the results of this research are 7M concentration and 1100C temperature using nitric acid solvent with a nickel recovery percent obtained of 23.14% and 20.71%